Café Imports Case Study – Building Sustainable Competitive Advantage Through Principled Entrepreneurship - Ebben, Jay; Johnson, Alec (Journal of Applied Business and Economics, 2021)
This case study was written to illustrate how a for-profit company can build sustainable competitive advantages via principled entrepreneurship. The case follows a recent college graduate’s journey at a mission-driven coffee importer and asks students to analyze how he developed strategic initiatives that align with the company’s core values. The case leaves students with three main perspectives: 1) Pursuit of the common good is not limited to not-for-profit firms; 2) Entrepreneurial firms do not need to sacrifice their core values in order to compete; and 3) Core values should be considered in commonly-used analysis frameworks such as Porter’s Five Forces.